UV-B STRESS INDUCED ALTERATION IN THE PHOTOSYNTHETIC APPARATUS OF THE CYANOBACTERIA SYNECHOCOCCUS 6301 - K. KUMAR; K. SURESH; D. S. KIRAN (The Bioscan, 2022)
Exposure of spheroplasts of the cyanobacteria Synechococcus 6301 to UV-B irradiance (5 Wm-2) stress for 0 to 60 minutes caused inhibition in various partial photochemical reactions. Compare to two photosystems (PS), PS II seems to be more susceptible to UV-B radiation than the PS-I. The results indicated that light haversting complex of PS II is the primary target for UV-B irradiation. It causes inhibition in Hill reaction by inducing the structural alterations in the spectral properties of phycobiliproteins.